2013
DOI: 10.1002/jssc.201300012
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitation of seven alkaloids in processed Fuzi decoction by rapid resolution liquid chromatography coupled with tandem mass spectrometry

Abstract: A rapid analytical method based on rapid resolution LC coupled with MS/MS was first established to quantify seven alkaloids in processed Fuzi decoction. The chromatographic method was optimized to allow simultaneous analysis of all analytes in 5 min and demonstrated good linearity (r > 0.9995), repeatability (RSD < 4.36%), intra- and interday precisions (RSD < 5.07%) with good accuracies (97.76-105.08%) and good recovery (95.0-107.5%) of seven alkaloids, namely higenamine, benzoylhypaconine, benzoylmesaconine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…4 In a recent quantitative analysis of processed Fuzi decoctions, including BFP, it was found that the contents of aconitine and mesaconitine were largely reduced by hydrolysis to monoester alkaloids during the processing, leading to a corresponding reduction in toxicity. 40 However, it now appears that at certain high doses of BFP, abundant amounts of the non-hydrolyzed toxic diester diterpene alkaloids still possess a certain degree of systemic toxicity, compensating for the NO-inhibitory potential of the cardioprotective alkaloid, higenamine.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a recent quantitative analysis of processed Fuzi decoctions, including BFP, it was found that the contents of aconitine and mesaconitine were largely reduced by hydrolysis to monoester alkaloids during the processing, leading to a corresponding reduction in toxicity. 40 However, it now appears that at certain high doses of BFP, abundant amounts of the non-hydrolyzed toxic diester diterpene alkaloids still possess a certain degree of systemic toxicity, compensating for the NO-inhibitory potential of the cardioprotective alkaloid, higenamine.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, higenamine has been detected in the decoctions Baifupian and Heishunpian in similar amounts ranging from 2.31 to 3.18 μg/g. [ 70 ]. Nowadays, there are many processed products of Aconitum .…”
Section: Resultsmentioning
confidence: 99%
“…Each concentration was analyzed in triplicate, and the calibration curves were established by plotting the peak areas versus the concentrations of each solution. The LOD and LLOQ were measured at signal-to-noise ratios (S/N) of 3 and 10, respectively, as per criteria from [50].…”
Section: Methodsmentioning
confidence: 99%
“…The equilibrium solubilities of the samples were determined by the shake-flask method [50]. Briefly, the accurately weighed solid sample was carefully added to 10 mL of the aqueous buffer in a glass vial and stirred at (37 ± 1) °C for 24 h. The aliquots of supernatant were taken out and diluted with solvent if necessary, and the concentration of sample in each aliquot was measured by UHPLC-TQ-MS.…”
Section: Methodsmentioning
confidence: 99%